2016
DOI: 10.1016/j.soscij.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The association of attitudes about contraceptives with contraceptive use in a random sample of Colorado women

Abstract: Context Research regarding unintended pregnancy often focuses on how women make decisions about whether or not to use contraceptives, and structural barriers to contraception. Less research examines how multidimensional attitudinal characteristics may be associated with effective contraceptive use. Methods In fall 2007, we conducted a random telephone survey of 801 sexually active women in Colorado to assess associations of the attitudinal dimensions of Planning, Partner Communication, and Stigma and Misinfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 33 publications
1
10
0
2
Order By: Relevance
“…Erroneous beliefs about modern contraceptives mainly included fear of them causing infertility and cancer. Such misconceptions were also found in other studies from Saudi Arabia [21], Nigeria [19], Tanzania [34], Sweden [11], the USA [20] and a global study on the IUS [35]. .…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Erroneous beliefs about modern contraceptives mainly included fear of them causing infertility and cancer. Such misconceptions were also found in other studies from Saudi Arabia [21], Nigeria [19], Tanzania [34], Sweden [11], the USA [20] and a global study on the IUS [35]. .…”
Section: Discussionsupporting
confidence: 70%
“…However, husbands usually do not attend the SRH clinics with their wives and therefore do not have the same access to accurate information about contraception. Their level of erroneous beliefs might be greater and at the same time have larger influence on the decision to use contraception; a trend also seen in other global studies [18, 20, 3638]. On the other hand, male support for contraceptive use increased female uptake [3941].…”
Section: Discussionmentioning
confidence: 69%
“…The "steps, stage, and statuses in dating relationships" during late adolescence and young adulthood are less clear than that of older adults (Owen et al 2010). Studies that have found an association between relationship status and contraceptive use have largely included participants beyond the age of women included in the present study (Higgins et al 2014, James-Hawkins andBroaddus 2016). Furthermore, relationship characteristics that were not captured in our survey, such as duration of relationship and parenthood status, are relevant to contraceptive use (Wilson and Koo 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Two decades after Pamela Erickson's study of low-income Hispanic youth in Los Angeles (1998) and in a very different context, the cultural trope Erickson identified of male pressure for sex and female acquiescence in many ways defined and constrained the experiences of the girls from the colonias. These young women communicated being raised with expectations of preserving their virginities throughout their teen years, a finding which accords with traditional Hispanic gender attitudes (Erickson, 1998;James-Hawkins & Broaddus, 2016;Jimenez et al, 2002). Their parents seemingly saw no need to educate them about contraception and may have even viewed a discussion about contraception as an invitation to begin having sex (García, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As such, an analysis of the cultural values to which Hispanic teens may potentially be exposed is important for understanding their sexual behaviors, including their sex, contraception, and pregnancy intentions. Such values may include conservative views of sexuality that lead community members to stigmatize teenage girls who plan for sex (Erickson, 1998; James-Hawkins & Broaddus, 2016; Jimenez, Potts, & Jimenez, 2002), eschew discussions with teens about contraception (García, 2012), or structure women as subordinate to men in sexual decision making (Gutmann, 2007). Pamela Erickson’s interviews with low-income teens from a variety of Hispanic subgroups in mid-1990s Los Angeles revealed a cultural sexual initiation script in which young men were expected to pressure for sex, and young women were expected to be ignorant about sex and resist at first but eventually acquiesce in a heat of the moment exchange that showed they had not been planning for sex (1998).…”
Section: Vagueness In the Consequences Causes And Intendedness Of Tmentioning
confidence: 99%